VCIN Vehicular Interconnected Informatics Network â€œA interconnected network of vehicular information, Data, and Interfaceâ€ - Tiwari, Vishaka; Saurav, Kumar; Safa, M (International Journal of Engineering and Technology, 2018)
With market moving towards smart city development, the importance of data and its analysis has increased. According to a report by HIS Market, data generated from IOT devices will increase to 125 billion in 2030. Such huge amount of data is going to bring opportunities for all level of industries and markets. Thus, intelligent collection of data along with storage, processing and analysis will be a key to develop smart city. The information generated through data can target both users and market. It will be a result of various machine learning, data mining algorithms and distributed data storage technologies. The users can access information through web/mobile applications. The real time analysis of data and delivering it to user with no time will reduce accidents. This will increase productivity in hardware and software markets .VCIN the system of interconnected network of vehicles and infrastructure model in which, it focuses on four core modules. The interconnecting modules makes the network of data coming in and out of the system and finally getting displayed on one of our dashboard.Â Â